Splat the Cat. Splat and Seymour, best friends forevermore - Scotton, Rob; Heyman, Alissa (Splat the Cat., 2014)
While planning a surprise party to show his best friend Seymour how much he values their friendship, Splat keeps so many secrets Seymour doesn't want to be friends anymore.